2015
DOI: 10.1149/06914.0033ecst
|View full text |Cite
|
Sign up to set email alerts
|

Towards Electrochemical Fabrication of Free-Standing Indium Phosphide Nanofilms

Abstract: Access to the full text of the published version may require a subscription.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…parallel to the secondary flat of the InP wafer). 1,2,4,57,58 This shows that individual, isolated porous domains form in the early stages of anodization. We have shown that each such domain is separated from the surface by a thin non-porous layer of dense InP [1][2][3][4] and is connected to the electrolyte by a single pit which penetrates this nearsurface layer.…”
mentioning
confidence: 89%
“…parallel to the secondary flat of the InP wafer). 1,2,4,57,58 This shows that individual, isolated porous domains form in the early stages of anodization. We have shown that each such domain is separated from the surface by a thin non-porous layer of dense InP [1][2][3][4] and is connected to the electrolyte by a single pit which penetrates this nearsurface layer.…”
mentioning
confidence: 89%
“…Figure 10 shows a series of LSVs of InP in KOH solutions varying from 2.0 to 1.0 mol dm -3 . The LPSs were stopped at an upper potential of 0.75 V because previous studies 41,42 have shown that the etching mechanism changes at higher potentials, resulting in the undercutting and removal of the porous layer. The shape of the LSV at 2.0 mol dm -3 KOH is similar to that seen for porous layer formation at lower temperatures in Fig.…”
Section: The Transition From Porous Layer Formation To Planar Etchingmentioning
confidence: 99%
“…If a sample which has been anodised for a short period of time (i.e., to between Ei and Ep1 of Fig. 5) is then chemically etched in a H2SO4 solution, all the porous structures including the internal skeletons of the domains can be removed [22] as shown in Fig. 6.…”
Section: Pit Initiation and Domain Expansion (Region Iia) Progressive...mentioning
confidence: 99%